If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + -5a = 13 Combine like terms: 6a + -5a = 1a 1a = 13 Solving 1a = 13 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '1'. a = 13 Simplifying a = 13
| 12p-16=-44+16p | | (p*p*p)-(1p*2p)=(p*p)+40p | | 4x^2=1764(-25x^2) | | 4x^2=1764-25x^2 | | 4x^2=-25x^2 | | 50+60+x+70=180 | | (p*p*p)-(2p*2p)=(p*p)+40p | | 4z+2+4z=10z-22 | | 5(u-8)-5=-3(-8u+9)-3u | | (6z-46)+33=5z+14 | | 3d+4(d-2)= | | x^2=7+2 | | 2x-10x-12=0 | | 4*3.14(x^2+25x+25)= | | 6t+42=7t+27 | | 5x^2+2x=175 | | 65=5+5x | | 3=2w+7 | | -14uv+4v-21u=0 | | -14uv+4v=o | | B(x)=40.00-0.06x | | 4d+2(d+6)=-3(d-4) | | -6v-4=-4(v-3) | | -71p+2p-9p+2+43= | | y=(-.0625)x^2+.375x+(-2.05) | | -6v-4=4(v-3) | | -6v-4=-4v(v-3) | | 10(3x-1)=-100 | | 3(v+3)=-8v-2 | | -16+x=8 | | 3y+48=-3(y+2) | | (16q+4)+42=29q+20 |